Evaluation of natural resources for conservation and recreation opportunities in greenway development of Setiu Wetland, Malaysia - Hamzah, Mohd Zakaria (2012)
Setiu Wetland is a unique nine inter-connected ecosystem that offers great opportunities for both recreation and wildlife conservation in Terengganu. However, conservation on the area is limited due to habitat fragmentation. Sustainable management is a possible solution to the problem. Such development may also support the State Government of Terengganu in terms of increasing revenue (or benefits) through ecotourism. The purpose of this study was to identify the greenway zone in Setiu Wetland, Terengganu for wildlife conservation and recreation opportunities using the greenway conceptual diagram model with the adaption of conceptual relation framework of wildlife conservation and recreation opportunities. The objective will be achieved through determination of vegetation and habitat mapping of Setiu Wetland, estimation of wildlife diversity, examination and comparison of wildlife composition between sites, examining the recreational resources in the area, and to propose the location to be zoned as greenway system on Setiu Wetland. Evaluations were made on 12 potential sites in Setiu Wetland consisting Avicennia-ceriops, beach forest/ Casuarina, coconut, mixed-mangrove and peat swamp habitats. Point-count methods, Sherman traps, casual observations and RRI were conducted on the sites. Data analysis involved the application of MVSP, Neighbour clustering technique and chi-square test. Based on the number of wildlife, their diversities, habitats density and the recreation resources found in the areas, the sites S1, S4, S5, S6, S7, S8, S9, and S10 were chosen to be the hubs of greenway, while S2, S3, S11 and S12 the links which connect these hubs from one to another to complete the greenway system. The results also indicated that there is a relationship between wildlife conservation and recreation opportunities in Setiu Wetland. Landscape linearity, connectivity and biodiversity not only provide conservation of wildlife in the area but also opportunities for recreation, ecotourism and nature study. Hence the implementation of greenway zone in Setiu Wetland is seen as highly feasible.